System alternatives for modular, zero-emission high-speed ferries - Lagemann, Benjamin; Seidenberg, Tobias; Jürgenhake, Christoph; Erikstad, Stein Ove; Dumitrescu, Roman (SNAME International Conference on Fast Sea Transportation)

D-REQs: Determination of security & safety requirements in workshops based on the use of model-based systems engineering - Japs, Sergej; Anacker, Harald; Kaiser, Lydia; Holtmann, Jörg; Dumitrescu, Roman; Kargl, Frank (Proceedings of the IEEE)

Smart factory reference model for training on Industry 4.0 - Mohammad, Ubaidullah; Low, Cheng; Rahman, Ramhuzaini Abd; Johar, Muhammad Akmal; Koh, Ching Theng; Dumitrescu, Roman; Rabe, Martin; Asmar, Laban; Kamaruddin, Susana (Journal of Mechanical Engineering (JMechE))

Peer-to-Peer Matching for Distributed Systems - Adsul, Vaibhav

Data-Driven Model for Upper Limb Spasticity Detection - Yee, Jingye; Low, Cheng Yee; Hashim, Natiara Mohamad; Hanapiah, Fazah Akhtar; Soh, Wei Shien; Zakaria, Noor Ayuni Che; Nemah, Mohammed Najeh; Asmar, Laban; Rabe, Martin; von Enzberg, Sebastian; Dumitrescu, Roman (International Journal of Integrated Engineering)

Selecting Features for the Next Release in a System of Systems Context - Wiecher, Carsten; Wolff, Carsten; Anacker, Harald; Dumitrescu, Roman (arXiv preprint)

Derivation of socio-technical solution patterns for industry 4.0 problem classes - Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Towards an ambidextrous innovation management maturity model - Niewöhner, Nadine; Lang, Nadja; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Integration of agile practices in the product development process of intelligent technical systems - Gabriel, Stefan; Niewöhner, Nadine; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Development Process for Smart Service Strategies: Grasping the Potentials of Digitalization for Servitization - Koldewey, Christian; Gausemeier, Jürgen; Dumitrescu, Roman; Evers, Hans Heinrich; Frank, Maximilian; Reinhold, Jannik (Digitalization)

Developing Strategies for Digital Transformation in SMEs with Maturity Models - Pierenkemper, Christoph; Gausemeier, Jürgen (Digitalization)

Identification and specification of standard modules in production for a material flow simulation - Henkenjohann, Mark; Joppen, Robert; Köchling, Daniel; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Iterative and Scenario-Based Requirements Specification in a System of Systems Context - Wiecher, Carsten; Greenyer, Joel; Wolff, Carsten; Anacker, Harald; Dumitrescu, Roman (Requirements Engineering: Foundation for Software Quality, REFSQ 2021)

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Krüger, Bettina; Nöthlings, Ute; Buyken, Anette E.; Alexy, Ute (European Journal of Clinical Nutrition)
Abstract Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at baseline, 45% females) having at least two measures of chronotype and anthropometry ( N = 572). Chronotype was assessed with the Munich Chronotype Questionnaire and defined as: midpoint of sleep corrected for sleep-debt (MSFsc) accumulated over the week (later MSFsc represents later chronotype). Social jetlag (SJL) defines the difference between midpoint of sleep during week and weekend. Calculations for Fat Free Mass Index (FFMI [kg/m 2 )]) and Fat Mass Index (FMI) [kg/m 2 )]) were based on body fat percentage, weight, and height. To analyze the associations, we used linear mixed-effect regression models. Finally, the total cohort was split into three biologically relevant age groups (cut-off set at <12 years, ≥12 to ≤15 years and >15 years). Results Median follow-up was 2.1 years. Overall, change toward a later chronotype was significantly related with an increase in FMI (ß: 0.05, 95% CI: 0.01–0.08). A 1 h increase in social jetlag predicted an increase in BMI-SDS of 0.08 SDS units (95% CI: 0.01–0.14) and in FMI of 0.04 kg/m2 (95% CI: 0.003–0.08). Associations were stronger for the age group ≥12 to ≤15 years ( p for interaction: <0.001). No relationship was found with FFMI. Conclusions Changes in MSFsc and SJL during adolescence were associated with concurrent changes in BMI-SDS and FMI. The age ≥12 to ≤15 years appears to be a sensitive period in which chronobiological changes were clearly associated with increasing body fatness.

Model of a Triangular Caterpillar Drive and Analysis of Vertical Vehicle Dynamics - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Russian Engineering Research)

Arbeit 4.0 in der Produktentstehung mit IviPep - Foullois, Marc; Kato-Beiderwieden, Anna-Lena; Mlekus, Lisa; Maier, Günter W.; Jenderny, Sascha; Röcker, Carsten; Dietz, Oliver; Pretzlaff, Matthias; Huxdorf, Oliver; von Dungern, Friedrich; Bräutigam, Dieter; Seifert, Lars; et al. (Arbeit in der digitalisierten Welt - Praxisbeispiele und Gestaltungslösungen aus dem BMBF-Förderschwerpunkt)

Platform Patterns - Using Proven Principles to Develop Digital Platforms - Drewel, Marvin; Özcan, Leon; Gausemeier, Jürgen; Dumitrescu, Roman (Journal of the Knowledge Economy)
Hardly any other area has as much disruptive potential as digital platforms in the course of digitalization. After serious changes have already taken place in the B2C sector with platforms such as Amazon and Airbnb, the B2B sector is on the threshold to the so-called platform economy. In mechanical engineering, pioneers like GE (PREDIX) and Claas (365FarmNet) are trying to get their hands on the act. This is hardly a promising option for small and medium-sized companies, as only a few large companies will survive. Small and medium-sized enterprises (SMEs) are already facing the threat of losing direct consumer contact and becoming exchangeable executers. In order to prevent this, it is important to anticipate at an early stage which strategic options exist for the future platform economy and which adjustments to the product program should already be initiated today. Basically, medium-sized companies in particular lack a strategy for an advantageous entry into the future platform economy. The paper presents different approaches to master the challenges of participating in the platform economy by using platform patterns. Platform patterns represent proven principles of already existing platforms. We show how we derived a catalogue with 37 identified platform patterns. The catalogue has a generic design and can be customized for a specific use case. The versatility of the catalogue is underlined by three possible applications: (1) platform ideation, (2) platform development, and (3) platform characterization.
Keywords: Digitalization; Digital platforms; Platform economy; Multisided markets; B2B platforms

Towards collaborative life cycle specification of digital twins in manufacturing value chains - Rasor, Rik; Göllner, Denis; Bernijazov, Ruslan; Kaiser, Lydia; Dumitrescu, Roman (Procedia CIRP)

Structuring Framework for Early Validation of Product Ideas - Asmar, Laban; Grigoryan, Khoren; Low, Cheng Yee; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (International Journal of Integrated Engineering)

Improving Real-World Applicability of Static Taint Analysis - Luo, Linghui